Quick Evaluation Study on Fourteen (14) Major Development Programmes in Malkangiri District of Orissa State Affected by Left Wing Extremism (LWE) - Planning Commission (Planning Commission, 2011)
"The evaluation report is done to appraise the impact of flagship schemes - Mahatama Gandhi National Rural Employment Guarantee Act, Pradhan Mantri Gram Sadak Yojana, Rajiv Gandhi Gram Vidyutikaran Yojana, Rajiv Gandhi National Drinking Water Mission, Sarva Shiksha Abhiyan, Integrated Child Development Services, Indira Awas Yojana, Targeted Public Distribution System, National Rural Health Mission, Ashram Schools and Hostels, Backward Region Grant Funds, land distribution under the Forests Act, Skill Development programmes - and also the influence of Maoism on these schemes. The district level report looks into the status of the above mentioned schemes into the five districts of Orissa - Deogarh, Gajapati, Malkangiri, Rayagada and Sambalpur."
"Programme Evaluation Organisation Planning Commission Government Of India New Delhi"